Homogeneous flow and size dependent mechanical behavior in highly ductile Zr65Ni35 metallic glass films. (1st June 2017) - Ghidelli, Matteo; Idrissi, Hosni; Gravier, Sébastien; Blandin, Jean-Jacques; Raskin, Jean-Pierre; Schryvers, Dominique; Pardoen, Thomas
Abstract: Motivated by recent studies demonstrating a high strength - high ductility potential of nano-scale metallic glass samples, the mechanical response of freestanding Zr65 Ni35 film with sub-micron thickness has been investigated by combining advanced on-chip tensile testing and electron microscopy. Large deformation up to 15% is found for specimen thicknesses below 500 nm with variations depending on specimen size and frame compliance. The deformation is homogenous until fracture, with no evidence of shear banding. The yield stress is doubled when decreasing the specimen cross-section, reaching ∼3 GPa for small cross-sections. The fracture strain variation is related to both the stability of the test device and to the specimen size. The study concludes on clear disconnect between the mechanisms controlling the onset of plasticity and the fracture process. Graphical abstract: Image